OpenStreetMap e la prima conferenza OSMit - Dellucchi, Luca; Rigacci, Niccolò; Cavallini, Paolo (GEOmedia, 2009)
OpenStreetMap and the first OSMit conference This month's article features a brief presentation of the OpenStreetMap project, initiated by a single user in 2004 with the aim of creating a free map of the world, editable following wiki-like rules, and evolved in a few years in a system involving over 100,000 users contributing data from all over the world. The interest in presenting this topic is related also to the recent occurrence of the first meeting of the Italian OpenStreetMap Community. The meeting took place in Trento in early June 2009, organized by the Fondazione Bruno Kessler, and demonstrated the liveliness of this community, showcasing experience conducted over the past year, and highlighting developments for the future.